2017
DOI: 10.1002/mrc.4681
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mobility in several imidazolium‐based ionic liquids according to data of 1H and 13C NMR relaxation

Abstract: Temperature dependences are compared for H and C NMR 1/T curves relaxation rates in three imidazolium-based ionic liquids (ILs), namely, in [bmim]PF , [bmim]BF , and [emim]CH COO. C curves show alike behavior for all three ILs and follow a well-known Bloembergen-Pound-Purcell (BPP) equation. On the contrary, an essential part of H curves differ strongly from corresponding C ones and also have different shapes for different ILs. For the first time, we have detected the specific, two-maximum shape of H relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A rotation/flip of the imidazolium core around N-C bond can also be accompanied by the chain re-alignment. The correlation of motion by ion-pairing, as has been observed in isotropic phase of ionic liquids, may impose additional restriction on the core dynamics [26][27][28][29]. On the other hand, diffusion and conductivity studies have indicated (partial) dissociation of cations and anions in mesophases [28][29][30].…”
Section: Order Parametersmentioning
confidence: 95%
“…A rotation/flip of the imidazolium core around N-C bond can also be accompanied by the chain re-alignment. The correlation of motion by ion-pairing, as has been observed in isotropic phase of ionic liquids, may impose additional restriction on the core dynamics [26][27][28][29]. On the other hand, diffusion and conductivity studies have indicated (partial) dissociation of cations and anions in mesophases [28][29][30].…”
Section: Order Parametersmentioning
confidence: 95%
“…A more detailed overview of works in the outlined area is presented in papers and reviews. ,,,,,, ,, Note in addition that in a series of works, Abe and co-authors hypothesized the existence of “water pockets” in the structure of solutions at a water concentration of approximately 70–90 mol %. It was reported that such formations manifested an abnormal behavior of water, and we discuss here the problem in details.…”
Section: Introductionmentioning
confidence: 99%
“…Some other significant results on IL/RTILs have been presented and discussed in many reviews. 4,7,19,20,30,64,65 Despite numerous works, some important gaps in studies still remain. One of those gaps is the absence of multinuclear NMR relaxation experiments for the wide series of neat RTILs with altering anions or cations, similar to what was done in the study of chemical shifts or self-diffusion coefficients.…”
Section: ■ Introductionmentioning
confidence: 99%